EPEN-08. THE TREM1 POSITIVE HYPOXIC MYELOID SUBPOPULATION IN POSTERIOR FOSSA EPENDYMOMA. (1st June 2021) - Willard, Nicholas; Donson, Andrew; Ritzmann, Timothy; Grundy, Richard; Jackson, Andrew; Hankinson, Todd; Griesinger, Andrea; Foreman, Nicholas
Abstract: We have previously shown the importance of immune factors in posterior fossa ependymoma (PF EPN). Recently, we found eight transcriptionally unique subpopulations of myeloid cells infiltrating PF EPN with one population particularly enriched in PFA1 tumors. This subpopulation, denoted as hypoxia myeloid subpopulation, is defined by genes associated with angiogenesis, hypoxia response, wound healing, cell migration, neutrophil activation, and response to oxygen levels. TREM1 (Triggering receptor expressed on myeloid cells 1) was found to be expressed almost exclusively within this hypoxia myeloid subpopulation. TREM1 encodes for a receptor belonging to the immunoglobulin superfamily that is expressed on myeloid cells, and stimulates neutrophil and monocyte inflammatory responses. However, single-cell RNAseq give little data suggesting location of cells within the tumor microenvironment. We performed immunohistochemistry (IHC) on our bank of 90 FFPE PFA EPN samples using TREM1 to characterize and identify the location of the hypoxia myeloid cells. The TREM1 positive cells have an ambiguous cytomorphology reminiscent of a monocyte with modest cytoplasm and a mono-lobated nucleus. IHC also showed that TREM1+ myeloid cells are largely localized to the interface of necrosis and viable tissue, most frequently in a perivascular and intravascular distribution. The latter finding suggests that the TREM1+ cells are derived from the bone marrow and that they may be associated with the mesenchymal tumor population (MEC), which we have previously described as being enriched in PFA1 tumors and localizing to perinecrotic zones. This is supported by parallel IHC analysis of subpopulation-specific markers in the same cohort of PFA EPN which showed the highest TREM1 correlation was with CAIX, a marker of MEC. In PFA matched primary/recurrent pairs, the proportion of TREM1+ cells were increased at recurrence in the majority of cases, suggesting an evolving interaction between this TREM1+ hypoxia myeloid subpopulation and neoplastic cells over the disease course.